Therapy of Organophosphate Poisoning via Intranasal Administration of 2-PAM-Loaded Chitosomes - Elmira A. Vasilieva; Darya A. Kuznetsova; Farida G. Valeeva; Denis M. Kuznetsov; Andrey V. Zakharov; Syumbelya K. Amerhanova; Alexandra D. Voloshina; Irina V. Zueva; Konstantin A. Petrov; Lucia Ya. Zakharova (Pharmaceutics, 2022)
Chitosan-decorated liposomes were proposed for the first time for the intranasal delivery of acetylcholinesterase (AChE) reactivator pralidoxime chloride (2-PAM) to the brain as a therapy for organophosphorus compounds (OPs) poisoning. Firstly, the chitosome composition based on phospholipids, cholesterol, chitosans (Cs) of different molecular weights, and its arginine derivative was developed and optimized. The use of the polymer modification led to an increase in the encapsulation efficiency toward rhodamine B (RhB; ~85%) and 2-PAM (~60%) by 20% compared to conventional liposomes. The formation of monodispersed and stable nanosized particles with a hydrodynamic diameter of up to 130 nm was shown using dynamic light scattering. The addition of the polymers recharged the liposome surface (from −15 mV to +20 mV), which demonstrates the successful deposition of Cs on the vesicles. In vitro spectrophotometric analysis showed a slow release of substrates (RhB and 2-PAM) from the nanocontainers, while the concentration and Cs type did not significantly affect the chitosome permeability. Flow cytometry and fluorescence microscopy qualitatively and quantitatively demonstrated the penetration of the developed chitosomes into normal Chang liver and M-HeLa cervical cancer cells. At the final stage, the ability of the formulated 2-PAM to reactivate brain AChE was assessed in a model of paraoxon-induced poisoning in an in vivo test. Intranasal administration of 2-PAM-containing chitosomes allows it to reach the degree of enzyme reactivation up to 35 ± 4%.